Caring for patients with traumatic injuries of the thoracic aorta. - Collins AS; Dinsmore D (Dimensions of Critical Care Nursing)
Trauma is a major cause of mortality and morbidity in the United States, with blunt traumatic injuries of the thoracic aorta continuing to occur despite the increased use of seatbelts and airbags. Emerging from crash analysis are effective interventions and provides increased awareness of the occult nature of these types of injuries. This article describes those interventions that healthcare providers must embed throughout the continuum of care for patients experiencing thoracic aortic injuries. Outcomes will be dependent upon the healthcare provider's knowledge of the physics of the event and the urgency of the diagnosis, as well as the ability to assess and manage all the variables involved. Current procedural issues are delineated and case studies are used to illustrate the processes of care needed by these patients.